STUDENTS’ PERCEPTIONS ON ENGLISH LEARNING THROUGH EUROWEEK PROGRAM - Eni Erawati br Pane; Rahayu Apriliaswati; Urai Salam (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThis study aims to find the students’ perceptions of the English learning program in Euroweek foundation in Poland. The design of this research is a descriptive study. The respondents of this research were 100 students of Euroweek from the year 2019/2020. The researcher collected the data by using a questionnaire. From this research, it can be concluded that the students have positive perceptions of the program. It was proved by the total of students score that their motivation reached 92,04%, their interest in the program reached 83,12%, and their satisfaction after joining the program was 87,32%. Moreover, the statement score of the motivation reached 95%, as for the interest aspect has great result with the score reached 80,4%, and the satisfaction statement reached 87%. These total scores determine that the English learning program in Euroweek was significantly impactful for the students, mostly in improving their speaking and listening skill through its integrated activities. Also, with a great potential to provide rich opportunities for exchanging individual worldviews, promoting cultural understanding, experiencing personal growth, and as well providing the need in Poland for English proficiency improvement.Keywords: English Camp, English Learning, Euroweek